Social Media Influence on the Millennial Generation's Civic Disposition - Novitasari, Novitasari (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2018)
The development of science and technology encourages most people to follow the changes that occur in the world including the use of the internet as a daily necessity. The internet has become inherent in human life, especially in the millennial generation today because it makes it easier to communicate and exchange information, including in Indonesia. However, the impact caused in the use of social media is not always realized by the user so that it can lead to something that is not desired. Therefore, this study aims to determine how the impact of the use of social media affects the civic disposition of users, especially the millennial generation. The research approach used is a qualitative research approach with descriptive research methods. The researcher collected data through observation, interviews, and documentation studies. The results of the study indicate that social media can support the strengthening of national integration because of some of its functions. The culture of mutual cooperation and the love of the country can grow and develop in the community, especially social media users. Then the researcher gave recommendations based on the findings of the research, namely the need for an anticipatory and selective attitude for all parties, especially social media users and other interested parties. Keywords: social media, millenial generation, civic disposition Abstrak Perkembangan ilmu pengetahuan dan teknologi mendorong sebagian besar manusia mengikuti perubahan yang terjadi di dunia termasuk penggunaan internet sebagai kebutuhan pokok sehari-hari. Internet telah melekat dalam kehidupan manusia terutama pada generasi millennial dewasa ini karena memudahkan berkomunikasi dan bertukar informasi termasuk di Indonesia. Akan tetapi, dampak yang ditimbulkan dalam penggunaan media sosial tidak selalu disadari oleh pengguna sehingga dapat mengarah pada sesuatu yang tidak dikehendaki. Penelitian ini bertujuan untuk mengetahui bagaimana dampak penggunaan media sosial berpengaruh terhadap civic disposition pengguna terutama generasi milenial. Pendekatan penelitian yang digunakan adalah pendekatan penelitian kualtitatif dengan metode penelitian deskriptif. Peneliti mengumpulkan data melalui observasi, wawancara, dan studi dokumentasi. Hasil penelitian menunjukkan bahwa media sosial dapat mendukung penguatan integrasi nasional karena beberapa fungsi yang dimilikinya. Budaya gotong-royong dan rasa cinta tanah air dapat tumbuh dan berkembang pada masyarakat terutama pengguna media sosial. Kemudian peneliti memberikan rekomendasi berdasar pada hasil temuan penelitian, yaitu perlunya sikap antisipatif dan selektif bagi semua pihak terutama pengguna media sosial dan pihak lain yang berkepentingan. Kata kunci: media sosial, generasi milenial, civic disposition